Study on NVH robustness evaluation method of high-mileage automobile based on systematic sampling. (4th June 2020) - Xiong, Jianqiang; Yuan, Le; Liao, Dingding; Wu, Jun
In order to study the Noise Vibration and Harshness (NVH) changing characteristics of high-mileage automobile, master the NVH variation regularity of high-mileage automobile, and improve the riding comfort of automobile, based on the principle of statistical analysis and the adaptability of different sampling methods, a robust evaluation method of NVH of high-mileage automobile based on systematic sampling is proposed. In this paper, the basic principle and system implementation steps of this method are described. An example is provided to illustrate the robustness evaluation process of high-mileage automobile vibration acceleration by using the method proposed, and requirements and precautions in using the method are pointed out. The method proposed in the paper can provide a theoretical basis and guidance for quantitative and qualitative evaluation of automobile NVH robustness.